Oligodendrocytes and Microglia: Key Players in Myelin Development, Damage and Repair - Kalafatakis, Ilias (Biomolecules, 2021)
Oligodendrocytes, the myelin-making cells of the CNS, regulate the complex process of myelination under physiological and pathological conditions, significantly aided by other glial cell types such as microglia, the brain-resident, macrophage-like innate immune cells. In this review, we summarize how oligodendrocytes orchestrate myelination, and especially myelin repair after damage, and present novel aspects of oligodendroglial functions. We emphasize the contribution of microglia in the generation and regeneration of myelin by discussing their beneficial and detrimental roles, especially in remyelination, underlining the cellular and molecular components involved. Finally, we present recent findings towards human stem cell-derived preclinical models for the study of microglia in human pathologies and on the role of microbiome on glial cell functions.